Tindak Tutur Kesantunan Guru dan Siswa dalam Pembelajaran Bahasa Indonesia di SMP Negeri 2 Sakra: Tinjauan Pragmatik - Badelah Badelah; Mahsun Mahsun; Burhanuddin Burhanuddin (Center of Language and Cultural Studies, 2019)
This study aims to describe the type, and speech act strategy of teacher and student politeness in learning Indonesian in class VIII SMP Negeri 2 Sakra. The method used for data collection, namely observation, recording, and interviews. The results of the study show: (1) formalities between teachers and students always pay attention to the speech events when speaking; (2) speakers are always prejudiced towards the speech partners; (3) speakers are able to distinguish between conveying situations, namely serious situations and joking situations; (4) the types of teacher and student directive speech acts in Indonesian language learning in the classroom in the form of governing and the type of expressive speech acts in the form of forgiveness, praise, and criticism, both types of speech acts are predominantly conducted by teachers and students; (5) speakers are always introspective in order to know exactly what the partners say or use; (6) the principle of politeness and directive type of speech applied by teachers and students in learning Indonesian, including (1) maxim of wisdom; and (2) maxim of praise; (7) directive and expressive speech action strategies used by teachers and students in learning Indonesian, directly and indirectly.